2021
DOI: 10.3390/d13120622
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Long-Jawed Spiders Reveals Multiple Colonization of the Caribbean

Abstract: Dispersal ability can affect levels of gene flow thereby shaping species distributions and richness patterns. The intermediate dispersal model of biogeography (IDM) predicts that in island systems, species diversity of those lineages with an intermediate dispersal potential is the highest. Here, we tested this prediction on long-jawed spiders (Tetragnatha) of the Caribbean archipelago using phylogenies from a total of 318 individuals delineated into 54 putative species. Our results support a Tetragnatha monoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Tetragnatha is a very speciose genus with 321 valid species/subspecies after this work and is among the most common and widespread spiders in the world (Levi 1981;Castanheira et al 2019;Čandek et al 2021;World Spider Catalog 2022). The genus includes species with characteristic cheliceral morphology, with long and numerous diagnostic teeth (see discussion on this structure in Castanheira et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Tetragnatha is a very speciose genus with 321 valid species/subspecies after this work and is among the most common and widespread spiders in the world (Levi 1981;Castanheira et al 2019;Čandek et al 2021;World Spider Catalog 2022). The genus includes species with characteristic cheliceral morphology, with long and numerous diagnostic teeth (see discussion on this structure in Castanheira et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…One such massive sampling in the Caribbean archipelago (http://www. islandbiogeography.org/) offered reconstructed biogeographic histories of numerous arachnid clades of varying dispersal propensities (Dziki et al, 2015;Agnarsson et al, 2016;C ̌andek et al, 2019;Tong et al, 2019;C ̌andek et al, 2020a;Chamberland et al, 2020;Crews and Esposito, 2020;C ̌andek et al, 2021;Shapiro et al, 2022). Such multi-clade studies can powerfully test the ultimate biogeographic hypotheses specific to a particular archipelago.…”
Section: Grand Challenge 5: Utilize Arachnids As Models In Ecological...mentioning
confidence: 99%
“…Dispersal ability also evolves and it may qualitatively change the patterns derived from IDH (Čandek et al, 2021). For example, on oceanic islands where there are few predators, the prey organisms have less need to flee, leading to the evolution of flightless phenotypes (Waters et al, 2020; Wright et al, 2016).…”
Section: Ecological and Evolutionary Factors Affecting The Patterns O...mentioning
confidence: 99%
“…Although the non‐linear dynamics of single speciation events have been well studied in evolutionary biology (Nosil et al, 2017; Yamaguchi & Iwasa, 2017b), the rate of recurrent speciation has not been considered with sufficient depth in the context of species diversity patterns. From classical to recent studies, life history traits other than dispersal propensity and clade age have been suggested as important contributors to the origin of species diversity (e.g., Čandek et al, 2021; Jablonski, 1986; Marin & Hedges, 2016). The IDH is an attractive and classical hypothesis in evolutionary ecology because it predicts biodiversity despite confounding factors and challenges.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%